2007
DOI: 10.1111/j.1365-294x.2007.03231.x
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐scale spatial genetic structure in mixed oak stands with different levels of hybridization

Abstract: Oaks are model species for the study of natural introgressive hybridization. High interfertility among oak taxa might result in collective evolution, through transpecific spread of advantageous alleles, challenging the standard concept of species. Nine highly polymorphic microsatellite (nuSSR) loci were analysed in three mixed oak populations of Quercus pyrenaica and Quercus petraea (Montejo, Somosierra and Robregordo) with different density and hybridization rates. Both leaf morphology and molecular markers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 86 publications
(84 reference statements)
2
54
0
Order By: Relevance
“…Genetically intermediate individuals may be the result of incomplete lineage sorting in recently diverged species and/or of past and contemporary interspecifi c gene fl ow. However, the spatial location of genetically intermediate individuals in the contact zones between species and accordance of genetic assignment with gene fl ow analyses suggested their origin from recent interspecifi c gene fl ow, rather than shared ancestral polymorphisms between species (Curtu et al 2007a, 2009, de Heredia et al 2009,Valbuena-Carabana et al 2007.…”
Section: Gene Flow Analyses In Mixed Oak Standsmentioning
confidence: 99%
“…Genetically intermediate individuals may be the result of incomplete lineage sorting in recently diverged species and/or of past and contemporary interspecifi c gene fl ow. However, the spatial location of genetically intermediate individuals in the contact zones between species and accordance of genetic assignment with gene fl ow analyses suggested their origin from recent interspecifi c gene fl ow, rather than shared ancestral polymorphisms between species (Curtu et al 2007a, 2009, de Heredia et al 2009,Valbuena-Carabana et al 2007.…”
Section: Gene Flow Analyses In Mixed Oak Standsmentioning
confidence: 99%
“…Moreover, the possibility that shared alleles represent ancestral segregating polymorphisms rather than the outcome of hybridization has been suggested (Muir and Schlö tterer, 2005; but see Lexer et al, 2006). Environmental variation, disturbance as well as the degree of contact between species can affect the frequency and the spatial distribution of hybrids in natural oak populations (Nason, 1992;Rushton, 1993;Howard et al, 1997;Dumolin-Lapègue et al, 1999;Dodd and Afzal-Rafii, 2004;Tovar-Sanchez and Oyama, 2004;Curtu et al, 2007;Valbuena-Carabañ a et al, 2007). Although hybridization between some oak species, such as the closely related species Quercus robur and Q. petraea, has been analyzed extensively for nuclear, chloroplast and mitochondrial variation, our understanding of the underlying processes is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous empirical studies have suggested that spatial heterogeneity could be a potential determinant of variation in FSGS (Valbuena-Carabaña et al, 2007;Born et al, 2008;Wang et al, 2011), its association with spatial aggregation and its ensuing effects on effective gene dispersal rates have rarely been measured. The few studies that aimed to quantify both the local distribution of individuals and genetic structure across plant populations found positive associations between the level of FSGS and spatial aggregation (Jacquemyn et al, 2009;Chung et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, for a given population density, several numerical simulation studies have shown that the spatial aggregation of adult plants generally increases the magnitude of FSGS compared with random or regular distributions (Doligez et al, 1998;Leblois et al, 2004;Robledo-Arnuncio and Rousset, 2010). Recent empirical studies have also shown that plant populations in fragmented habitats exhibit stronger FSGS than in continuous habitats (see, for example, Valbuena-Carabaña et al, 2007;Wang et al, 2011; but see Born et al, 2008). However, empirical studies examining variation in FSGS among populations with different densities and degrees of spatial aggregation remain scarce (Hamrick and Trapnell, 2011), and FSGS has not been analysed together with the spatial distribution of individuals and microhabitat heterogeneity (but see Chung et al, 2007;Jacquemyn et al, 2009;Van Heerwaarden et al, 2010).…”
Section: Introductionmentioning
confidence: 99%